แนวทางการเตรียมพร้อมฉุกเฉินสำหรับอุบัติเหตุของการดำเนินการโรงไฟฟ้านิวเคลียร์ : กรณีศึกษาสถานที่ตั้งบ้านแหลมแท่นสำหรับโครงการโรงไฟฟ้านิวเคลียร์ในประเทศไทย - กชกร ศิริรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
This study was aimed at preparing the emergency guideline for response preparedness for the nuclear power plant (NPP) project in Thailand. The development of the guideline was based mainly on the International Atomic Energy Agency’s technical document no. 953, emergency category 1. The emergency plans by Scotland, Belgium and Canada were also considered. The proposed guideline covered the infrastructure elements, the functional elements and the urgent protective actions. Some parts of the plan were adopted from Thailand’s national civil defense plan. In addition, the calculation predicting the atmospheric dispersion of radioactive particles under the assumption of the nuclear accident at the proposed NPP site, Ban Laem Thaen, Chumporn province was also attempted. The result from the prediction was the primary information that could be used for preparing the urgent protective actions i.e. sheltering, evacuation, iodine prophylaxis, temporary relocation and permanent resettlement plans.